A magyar adóigazgatási eljárások és szolgáltatások digitalizációjának jogi és társadalmi kerete, kihívásai : A magyar e-adóigazgatási szabályozás eIDAS „forrása”, szabályrendszere és a magyar társadalom digitalizációs tudatossága, érettsége (The legal and social framework of the digitalization of Hungarian tax administration procedures and services, its challenges : The Hungarian e-tax administration regulation, its eIDAS ’source’, regulatory system, and the digital awareness and readiness of Hungarian society) - István Szalóki (KözigazgatásTudomány)
In this paper, I would like to present the last, almost one decade European Community law and social framework which effected the digital transformation of tax administration processes and services by the hungarian tax administration. My goal first of all is not to present detailed regulation or each services details, but also I would explain this frame of law regulation causes, reasons, on the basis of which the Hungarian tax authority or the tax authority of any member state „relied on Itself” during the development of electronic tax administration procedures. The Community legal regulation in this area can be considered to deficient, but flexible from another point of view. The regulation’s bigest mistake that it looks like the policies first of all technicals, informaticals are in nature, while their legal contents, legal effects are „theoreticals” or missing. The Communtiy law’s creator gives that appearance that the first goal is use of the technology, secondly the user matters, who really use it. In addition, it cannot be neglected either, the fact that the direction and degree of the digital transformation is essentially determined by the digital maturity of the given society. The society’s opinion make a really huge effect that a tax administration re-controll its result of work. If the society’s maturity of digitalization is not high enough than this calculation maybe give a wrong result. In this study, I aim to present these factors in a summary manner.